Histologically confirmed pediatric extracardiac rhabdomyoma: case series - Gashaw Arega; Abdulkadir Mohamedsaid; Getasew Fikad; Mulualem Nigusie; Tihitena Nigusie; Abrehet Zeray; Fathia Omer; Yodit Abraham; Alemayehu Tsega; Amanuel Damie; Tseganesh Mekonnen Hailemariam; Mesfin Asefa (Discover Oncology)
Abstract Rhabdomyoma is a rare benign tumor of striated muscle, which can be either cardiac or extracardiac. Extracardiac rhabdomyomas can occur throughout the body, though the fetal and adult subtypes are most commonly found in the head and neck region. We present three pediatric cases of extracardiac rhabdomyoma, fetal subtype, detailing their clinical presentations, computed tomography imaging, and tissue biopsy findings. Given the very rare occurrence of extracardiac rhabdomyoma and its relatively benign nature, histological diagnosis is crucial. In all three cases reported here, a diagnosis of extracardiac rhabdomyoma was confirmed, and treatment with local excision resulted in favorable outcomes.